U se of Mist-Netting Technique to Study Community Structure of l nderstory Birds at Lubok Tapah Base tamp, Endau-Rompin National Park, Johore, Malaysia - R. Hashim, Rosli Ramli,; Daicus, B. (Malaysian Journal of Science, 2004)
Mist netting technique was used to study the community structure of understory bird presence in Lubok Tapah base camp, Endau-Rompin National Park, Johore. Two hundred and six individuals who comprised 62 species from 16 families were captured. A majority of bird species that were captured after 1840 net-hours operation were residents (90.3%) and smaller birds (48.3%). Three families, namely Timalidae (babbler), Pycnonotidae (bulbuls) and Muscicapidae (flycatcher) were abundantly sampled. The most abundant species, however, were Yellow-Bellied Bulbul (Criniger phaeocephalus), Grey-headed Babbler (Stachyris poliocephala) and Rufous- collared Kingfisher (Halcyon concretd).